Diagnosis of slight and subacute coronary attacks in the community. Issue 3 (March 1981) - Short, D
Abstract : A series of 456 episodes of spontaneous chest pain not considered by the primary medical attendant to be sufficiently severe or suggestive of coronary disease to warrant admission to hospital has been studied prospectively in an attempt to provide guidelines for diagnosis and management. A final diagnosis of acute myocardial infarction was made in 40 per cent, spontaneous (or unstable) angina in 15 per cent, doubtful coronary attack in 12 per cent, and non-coronary chest pain in 33 per cent of the episodes. A diagnosis of myocardial infarction or spontaneous angina could never be made on the basis of a single feature, but demanded careful evaluation of the total evidence provided by the site and character of the chest pain, the associated symptoms, the clinical findings, and the electrocardiogram. A guide to diagnosis based on the findings of this study is set out in Tables 7 and 8.